(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This conceptual paper proposes a framework to explain customer loyalty formation in e-commerce, focusing on Shopee. Through the integration of Expectation–Confirmation Theory (ECT) and Service Quality Theory (SERVQUAL), the model investigates how customer satisfaction and complaint resolution affect customer loyalty. This work fills a conceptual gap caused by contradictory findings in previous research on these links. According to the framework, better service quality and efficient complaint resolution raise customer happiness, which in turn boosts loyalty. In addition to providing practical advice for e-commerce managers on how to create service plans that enhance customer experiences and cultivate long-term loyalty, the article makes a theoretical contribution by extending SERVQUAL and ECT into the digital realm.